Geographic information science & systems - Longley, Paul. (2015)
"Effective use of today's powerful GIS technology requires an understanding of the science of problem-solving that underpins it. Since the first edition published over a decade ago, this book has led the way, with its focus on the scientific principles that support GIS usage. It has also provided thorough, upto- date coverage of GIS procedures, techniques and public policy applications. This unique combination of science, technology and practical problem solving has made this book a best-seller across a broad spectrum of disciplines. This fully updated 4th edition continues to deliver on these strengths"--
Machine generated contents note: FOREWORD DEDICATION PREFACE LIST OF ACRONYMS 1 Geographic Information: Science, Systems, and Society 2 The Nature of Geographic Data 3 Representing Geography 4 Georeferencing 5 Uncertainty 6 GI System Software 7 Geographic Data Modeling 8 Data Collection 9 Creating and Maintaining Geographic Databases 10 The GeoWeb 11 Cartography and Map Production 12 Geovisualization 13 Spatial Data Analysis 14 Spatial Analysis and Inference 15 Spatial Modeling with GI Systems 16 Managing GI Systems 17 Information and Decision-making 18 Navigating the Risks 19 Epilogue: GISS in the Service of Humanity INDEX.
Includes index.
Keywords: Geographic information systems; TECHNOLOGY & ENGINEERING / Remote Sensing & Geographic Information Systems